Effect of Dietary Supplement from Lymphoid Tissue of Chickens on Cell Viability - Natalia A. Kolberg; Natalia V. Tikhonova; Sergei L. Tikhonov; Svetlana A. Leontieva (Техника и технология пищевых производств)
Introduction. Today, dietary supplements are an integral part of human diet. Some of them are made of hydrolysates of animal origin. Biologically active additives of immunomodulatory action can prevent various diseases. The research objective was to develop a dietary supplement from the bursa of Fabricius obtained from broiler chickens and evaluate its effect on cell viability in culture. Study objects and methods. The study featured biologically active supplement obtained by enzymatic hydrolysis of the bursa of Fabricius, immature stem cells, and adult differentiated cells of human dermal fibroblasts, HeLa and MCF-7 cancer cells, and extract of the bursa of Fabricius. Results and discussion. The research resulted in a new technology of dietary supplement production from the bursa of Fabricius of broiler chickens. It included washing, cutting, homogenization, proteolytic enzyme fermentation, and ultrafiltration. When introduced into the culture of mesenchymal stem cells, the dietary supplement caused a slight decrease in the cell viability at concentrations of 25 and 50%, which indicated a possible cytotoxic effect of the extract on mesenchymal cells. The extract did not affect the viability of human fibroblast culture and caused no cytotoxic effect. In MCF-7 culture, the extract had a dose-dependent cytotoxic effect, which lowered the relative cell viability. Conclusion. The new dietary supplement based on the bursa of Fabricius of broiler chickens had a cytotoxic effect on stem cell cultures. However, it did not affect the cell viability and had no cytotoxic effect on human dermal fibroblasts. The effect depended on the cell culture. In the case of HeLa, the supplement stimulated proliferative activity, and in the case of MCF-7, it had a cytotoxic effect. Therefore, the new dietary supplement demonstrated some prospects as an active ingredient for various biologically active additives and immunomodulatory drugs.